COVID-19 Vaccine Hesitancy in Pakistan: A Mini Review of the Published Discourse - Khalid, Sumaira; Usmani, Bilal Ahmed; Siddiqi, Sameen (Frontiers in Public Health, 2022)
This minireview provides a summary of the main findings, features, as well as limitations and gaps in the current epidemiologic research on covid-19 vaccine hesitancy (VH) in Pakistani population. For this purpose, data on VH studies were extracted from January 2020 to October 2021, using a systematic review and meta-analysis approach. Literature review and other narrative studies were excluded. There exists a significant heterogeneity in the reported vaccine hesitancy in the population (pooled estimates from random-effects meta-analysis: 35% (95% CI, 28% - 43%). However, none of the co-variables included in the studies explained the observed variance/heterogeneity in the moderator analysis models. In this minireview and critical appraisal of current VH research, we conclude that an in-depth analysis of covid-19 vaccine hesitancy in a representative sample of Pakistani population is crucial to measure the magnitude of VH as well to explore and identify the determinants of VH in Pakistani population. This is an important step toward informing intervention and policy design and to address this issue at its root cause. To this end, focused, methodologically robust and hypothesis-driven VH research is needed using a wide range of co-variables to support a detailed coverage of the individual and environmental level VH attributes.